An Identical Twin Study on Human Achilles Tendon Adaptation: Regular Recreational Exercise at Comparatively Low Intensities Can Increase Tendon Stiffness - Sichting, Freddy; Kram, Nicolai C.; Legerlotz, Kirsten (Frontiers in Physiology, 2022)
Achilles tendon adaptation is a key aspect of exercise performance and injury risk prevention. However, much debate exists about the adaptation of the Achilles tendon in response to exercise activities. Most published research is currently limited to elite athletes and selected exercise activities. Also, existing studies on tendon adaptation do not control for genetic variation. Our explorative cross-sectional study investigated the effects of regular recreational exercise activities on Achilles tendon mechanical properties in 40 identical twin pairs. Using a handheld oscillation device to determine Achilles tendon mechanical properties, we found that the Achilles tendon adapts to regular recreational exercise at comparatively low intensities by increasing its stiffness. Active twins showed a 28% greater Achilles tendon stiffness than their inactive twin sibilings (p < 0.05). Further, our research extends existing ideas on sport-specific adaptation by showing that tendon stiffness seemed to respond particularly well to exercise activities that included an aerial phase such as running and jumping. Interestingly, the comparison of twin pairs revealed a high variation of Achilles tendon stiffness (305.4 to 889.8 N/m), and tendon adaptation was only revealed when we controlled for genetic variance. Our results challenge the current view that high tendon strains are needed to induce tendon stiffness adaptation. The results also offer new insights into the impact of genetic variation on individual Achilles tendon stiffness, which should be addressed more closely in future studies.